2017
DOI: 10.1093/glycob/cwx022
|View full text |Cite
|
Sign up to set email alerts
|

The N-glycosylation of immunoglobulin G as a novel biomarker of Parkinson's disease

Abstract: The use of the emerging "omics" technologies for large scale population screening is promising in terms of predictive, preventive and personalized medicine. For Parkinson's disease, it is essential that an accurate diagnosis is obtained and disease progression can be monitored. Immunoglobulin G (IgG) has the ability to exert both anti-inflammatory and pro-inflammatory effects, and the N-glycosylation of the fragment crystallizable portion of IgG is involved in this process. This study aimed to determine whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
78
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 47 publications
9
78
2
Order By: Relevance
“…Two explanations could have been proposed for this surprising finding: either, enzymes encoded by FUT3/FUT6 locus exhibit non-canonical activity of core fucosylation, or that some IgG glycans actually do contain antennary fucose. Recently, the latter was demonstrated in work by Russell et al [14]. Our work does not show any evince for association between FUT3/FUT6 locus and core fucosylation, hence providing an independent evidence that explanation of association between FUT3/FUT6 and IgG glycosylation is rooted in presence of antennary fucose on some IgG glycans.…”
Section: Discussionsupporting
confidence: 66%
“…Two explanations could have been proposed for this surprising finding: either, enzymes encoded by FUT3/FUT6 locus exhibit non-canonical activity of core fucosylation, or that some IgG glycans actually do contain antennary fucose. Recently, the latter was demonstrated in work by Russell et al [14]. Our work does not show any evince for association between FUT3/FUT6 locus and core fucosylation, hence providing an independent evidence that explanation of association between FUT3/FUT6 and IgG glycosylation is rooted in presence of antennary fucose on some IgG glycans.…”
Section: Discussionsupporting
confidence: 66%
“…''Population Glycomics'' is one of the new and emerging approaches to biomarker discovery for common complex diseases. For example, studies in various world populations have found changes in IgG glycosylation in relation to, for example, metabolic syndrome (Lu et al, 2011), lung cancer (Chen et al, 2013), colorectal cancer (Vuckovic et al, 2016), Parkinson's disease (Russell et al, 2017), hypertension (Liu et al, 2018b), and T2DM (Lemmers et al, 2017). Itoh et al (2007) reported minute increments in an N-glycan with a1,6core-fucose within the total N-glycome that was associated with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous variables included age (Kristic et al, 2014;Yu et al, 2016) and BMI (Nikolac et al, 2014;Russell et al, 2019), and the categorical variables included hypertension (HT) (Wang et al, 2016), type 2 diabetes (T2D) (Lemmers et al, 2017), dyslipidemia (DL) (Liu et al, 2018a), cardiovascular disease risk score (CDRS) (Menni et al, 2018), ischemic stroke (IS) (Liu et al, 2018b), Parkinson's disease (PD) (Russell et al, 2017), nonalcoholic fatty liver disease (NAFLD) (Zhao et al, 2018), ulcerative colitis (UC) (Trbojevic et al, 2015), Crohn's disease (CD) (Trbojevic et al, 2015), systemic lupus erythematosus (SLE) (Vuckovic et al, 2015), rheumatoid arthritis (RA) (Gudelj et al, 2018b;Sebastian et al, 2016), chronic kidney disease (CKD) (Barrios et al, 2016), and colorectal cancer (CRC) (Vuckovic et al, 2016).…”
Section: Study Characteristicsmentioning
confidence: 99%